2015
DOI: 10.1080/2162402x.2015.1123366
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of TGFβ and PDGF signaling attenuates radiation-induced pulmonary fibrosis

Abstract: Background: Radiotherapy (RT) is a mainstay for the treatment of lung cancer, but the effective dose is often limited by the development of radiation-induced pneumonitis and pulmonary fibrosis. Transforming growth factor β (TGFβ) and platelet-derived growth factor (PDGF) play crucial roles in the development of these diseases, but the effects of dual growth factor inhibition on pulmonary fibrosis development remain unclear. Methods: C57BL/6 mice were treated with 20 Gy to the thorax to induce pulmonary fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 57 publications
1
55
0
Order By: Relevance
“…In preclinical experiments, TGF-b inhibitors have been shown to protect mice from pulmonary fibrosis following 20 Gy of ionizing radiation delivered to the thorax. 20 Consequently, our findings may suggest how mechanistically PLDR is associated with a reduced incidence of pulmonary side-effects following chest radiation. These in vivo data reinforce the clinical point that PLDR radiation is qualitatively different from conventional radiotherapy in terms of normal tissue injury.…”
Section: Resultsmentioning
confidence: 94%
“…In preclinical experiments, TGF-b inhibitors have been shown to protect mice from pulmonary fibrosis following 20 Gy of ionizing radiation delivered to the thorax. 20 Consequently, our findings may suggest how mechanistically PLDR is associated with a reduced incidence of pulmonary side-effects following chest radiation. These in vivo data reinforce the clinical point that PLDR radiation is qualitatively different from conventional radiotherapy in terms of normal tissue injury.…”
Section: Resultsmentioning
confidence: 94%
“…Platelets have been studied for decades as an important regulator of inflammation and thrombosis (34), which are broadly interrelated with human carcinogenesis (13). Platelets are also recognized as a stimulator of proangiogenic factors (13) and a major source of VEGF (35), platelet-derived growth factor (36,37), and basic fibroblast growth factor (37), which act as promoters of tumor growth in lung (38)(39)(40)(41)(42)(43)(44). New evidence suggests that platelets are relevant to defensive, physiologic immune responses of the lungs and to inflammatory lung diseases (45).…”
Section: Discussionmentioning
confidence: 99%
“…The candidate genes are usually those involved in DNA repair such as excision repair crosscomplementing (ERCC), X-ray repair cross complementing (XRCC), and so on (18,19), in inflammation such as transforming growth factor beta 1 (TGF-β1) and tumor necrosis factor alpha (TNFα), in oxidative stress, and in apoptotic pathways such as p53. Many studies have reported potential SNPs in these genes that are associated with radiation toxicities (20,21).…”
Section: Genomic Biomarkersmentioning
confidence: 99%